Bioequivalence and comparative pharmacodynamics of insulin lispro 200 U/mL relative to insulin lispro (Humalog®) 100 U/mL. Issue 1 (5th October 2015) - de la Peña, Amparo; Seger, Mary; Soon, Danny; Scott, Adam J.; Reddy, Shobha R.; Dobbins, Michael A.; Brown‐Augsburger, Patricia; Linnebjerg, Helle
Abstract: Insulin lispro 200 U/mL (IL200) is a new strength formulation of insulin lispro (Humalog®, IL100), developed as an option for diabetic patients on higher daily mealtime insulin doses. This phase 1, open‐label, 2‐sequence, 4‐period crossover, randomized, 8‐hour euglycemic clamp study aimed to demonstrate the bioequivalence of IL200 and IL100 after subcutaneous administration of 20 U (U) to healthy subjects (n = 38). Pharmacokinetic (PK) and pharmacodynamic (PD) responses were similar in both formulations. All 90%CIs for the ratios of area under the concentration‐versus‐time curve from time zero to the time of the last measurable concentration (AUC0–tlast ) and maximum observed drug concentration (Cmax ), as well as the total glucose infused throughout the clamp (Gtot ) and the maximum glucose infusion rate (Rmax ), were contained within 0.80 and 1.25. Time of maximum observed drug concentration (tmax ) was similar between formulations, with a median difference of 15 minutes and a 95%CI of the difference that included zero. Inter‐ and intrasubject variability estimates were similar for both formulations. Both formulations were well tolerated. IL200 was bioequivalent to IL100 after subcutaneous administration of 20‐U single doses, and PD responses were comparable between formulation strengths.